The association between attention control, anxiety, and depression: the indirect effects of repetitive negative thinking and mood recovery. Issue 4 (4th July 2017) - Kertz, Sarah J.; Stevens, Kimberly T.; Klein, Keith P.
ABSTRACT: Background and objectives: Attention control deficits and repetitive negative thinking (RNT; i.e., rumination) may be key factors in the development and persistence of depression and anxiety, although their role in symptom development remains poorly understood. This represents a gap in the literature, as interventions targeting attention control and associated RNT may enhance interventions and prevent costly relapse. The current study was designed to examine the serial indirect effects of transdiagnostic RNT and negative affect recovery following a lab-induced stressor on the association between attention control deficits and trait anxiety and depression. Methods: Participants were N = 583 university students who completed validated measures of RNT, anxiety, depression, and mood ratings pre- and post-stressor. Stress was induced using a modified version of the Trier Social Stress Test. Results: Results of cross-sectional indirect effects models indicated that RNT and mood recovery explained the association between attention control deficits and trait anxiety and depression. Results from reversed models indicated that only the indirect effect of RNT was significant. Conclusions: Findings suggest that RNT and mood recovery processes play an important role in explaining anxiety and depression symptoms. Additional work is needed to examine their role in symptom development and maintenance over time.